Ionic Polymer Microspheres Bearing a CoIII–Salen Moiety as a Bifunctional Heterogeneous Catalyst for the Efficient Cycloaddition of CO2 and Epoxides. Issue 24 (26th April 2016) - Leng, Yan; Lu, Dan; Zhang, Chenjun; Jiang, Pingping; Zhang, Weijie; Wang, Jun
Abstract: We report a unique strategy to obtain the bifunctional heterogeneous catalyst TBB‐Bpy@Salen‐Co (TBB=1, 2, 4, 5‐tetrakis(bromomethyl)benzene, Bpy=4, 4'‐bipyridine, Salen‐Co= N, N '‐bis(4‐dimethylaminosalicylidene)ethylenediamino cobalt(III) acetate) by combining a cross‐linked ionic polymer with a Co III –salen Schiff base. The catalyst showed extra high activity for CO2 fixation under mild, solvent‐free reaction conditions with no requirement for a co‐catalyst. The synthesized catalyst possessed distinctive spherical structural features, abundant halogen Br − anions with good leaving group ability, and accessible Lewis acidic Co metal centers. These unique features, together with the synergistic role of the Co and Br − functional sites, allowed TBB‐Bpy@Salen‐Co to exhibit enhanced catalytic conversion of CO2 into cyclic carbonates relative to the corresponding monofunctional analogues. This catalyst can be easily recovered and recycled five times without significant leaching of Co or loss of activity. Moreover, based on our experimental results and previous work, a synergistic cycloaddition reaction mechanism was proposed. Abstract : This cat has five lives : Novel ionic polymer microspheres bearing a Co III –salen moiety were demonstrated to be highly efficient catalysts (high activity, easy recovery, and reusable) for the cycloaddition reaction of CO2 and epoxides (see figure).